DAMPAK NAUNGAN TERHADAP PERUBAHAN KARAKTER AGRONOMI DAN MORFO-FISIOLOGI DAUN PADA TANAMAN KEDELAI (Glycine max (L.) Merrill) - Chairudin Chairudin; Efendi Efendi; Sabaruddin Sabaruddin (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
Shade is one of the obstacles in the cultivation of soybean crops in intercropping systems. This study was aimed at determining the change in the characters of agronomic and morpho-physiological leaves of soybean plants due to shade. The experiment was conducted at the Experimental Farm of Agriculture Faculty, Teuku Umar University Meulaboh in West Aceh, from August to November 2013. The experiment was arranged in a split plot design with three replications, where subplot (varieties: Anjasmoro, Kipas Merah Bireun, Grobogan, Burangrang, Sinabung, Kaba) was nested in the main plot (shade: without shade, 25% and 50% shade). The results showed that the shade and varieties exerted high significant effects on changes in agronomic characters and morpho-physiological leaf variables, except 100-seed weight and ratio of chlorophyll a/b which were not affected by shade and the amount of chlorophyll b and the ratio of chlorophyll a/b not affected by varieties. Interactions between shade and varieties were highly significant on changes in agronomic characters, except variables 100-seed weight.